Weed-based liquid organic fertilizer increased growth and yields of organically grown sweet corn - Fahrurrozi, F.; Setyowati, N.; Sudjatmiko, S.; Muktamar, Z.; Chozin, M. (International Journal of Agricultural Technology, 2024)
Results indicated that the use of weed-based liquid organic fertilizer (LOF) elevated sweet corn growth and yield. The use of weed-based LOF had a greater impact on generative growth than on vegetative growth of sweet corn. The best concentration of LOF for increasing plant height, fresh weight of unhusked ear, length of unhusked ear, and sweetness level of sweet corn were 57 %, 68 %, 72 %, and 76 %, respectively. These results are provided important information about how the use of weeds in LOF production for maximizing production of organic sweet corn